Cu/Zn superoxide dismutase homologs participate in Nicotiana benthamiana antiviral responses - Wang, Haijuan; Zhang, Jidan; Meng, Zhuo; Sun, Zhenqi; Liu, Dongyang; Li, Bin; Yan, Fangfang; Jia, Chongyi; Zhou, Hongyou; Zhao, Mingmin (Frontiers in Microbiology, 2025)
Superoxide dismutases (SODs) serve as the first line of defense against reactive oxygen species. Copper-zinc superoxide dismutase (Cu/Zn-SOD) is an enzyme whose activity depends on copper availability. Cu/Zn-SOD-1 induction is shown to be involved in the antioxidative and antiviral activity of acetylsalicylic acid in hepatitis C virus (HCV)-expressing cells. Here, RNA sequencing (RNA-seq) analysis identified SOD homologs (three NbCu/Zn-SOD, four NbFe-SOD, and two NbMn-SOD) that were differentially expressed in Nicotiana benthamiana during tobacco vein mottling virus (TVMV) infection. NbCu/Zn-SOD-1 was cloned from N. benthamiana and subsequently characterized. Encoding sequence and structural analyses of the NbCu/Zn-SOD-1 protein confirmed a conserved SOD enzyme domain, GFHLHEfGDtT, indicating that it is SOD-dependent and phylogenetically related to Cu/Zn-SOD in Nicotiana tabacum (XP 016486719.1). NbCu/Zn-SOD-1 was primarily localized in the cytoplasm. The transient expression of NbCu/Zn-SOD-1 led to a reduced accumulation of TVMV and PVY-Rosea1 (PVY-Ros1). In summary, our results suggest that NbCu/Zn-SOD-1 homologs participate in plant antiviral responses.